Financial Vulnerability among Central Java's Middle Class: The Roles of Digital Financial Literacy, Attitude, and Behaviour - Ika Neni Kristanti; Syafri Nurrochman; Aris Susetyo (Academic Bright Collaboration, 2026)
Purpose – This study aims to examine the influence of Digital Financial Literacy and Financial Attitude on Financial Vulnerability through Financial Behavior among middle-class individuals in Central Java. The study was conducted due to the increasing use of digital financial services, which may simultaneously improve financial access and increase financial risks among middle-class communities. Methods – This study employed a quantitative approach using primary data collected through questionnaires distributed to 220 middle-class respondents in Central Java. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among variables. Findings – The results indicate that Digital Financial Literacy positively and significantly affects Financial Behavior (β = 0.320, p < 0.001), and Financial Attitude also positively affects Financial Behavior (β = 0.230, p = 0.002). Digital Financial Literacy was found to have a positive and significant association with Financial Vulnerability (β = 0.654, p < 0.001), contrary to the proposed hypothesis. Meanwhile, Financial Attitude (β = -0.004, p = 0.930) and Financial Behavior (β = 0.097, p = 0.075) do not significantly affect Financial Vulnerability. Furthermore, Financial Behavior does not mediate the relationships between Digital Financial Literacy and Financial Vulnerability (β = 0.031, p = 0.132) nor between Financial Attitude and Financial Vulnerability (β = 0.022, p = 0.130). Research implications – The findings imply that improving digital financial literacy alone may not be sufficient to reduce Financial Vulnerability among middle-class individuals. Policymakers and financial institutions should not only focus on expanding digital financial access and literacy programs but also strengthen financial risk awareness, consumer protection, and responsible digital financial practices. The results also indicate the importance of monitoring the potential negative consequences of excessive digital financial service utilization, such as impulsive spending and overreliance on digital credit facilities. Originality – This study contributes to the Financial Vulnerability literature by highlighting that higher digital financial literacy does not necessarily reduce Financial Vulnerability in the digital era. The findings suggest that increased exposure to digital financial services may simultaneously create greater financial risks for middle-class individuals.